ПОРІВНЯЛЬНА ОЦІНКА ТРАНСФОРМАТОРНО-КЛЮЧОВИХ ВИКОНАВЧИХ СТРУКТУР ДИСКРЕТНИХ СТАБІЛІЗАТОРІВ ТА РЕГУЛЯТОРІВ НАПРУГИ ЗМІННОГО СТРУМУ - Липківський, К.О.; Халіков, В.А.; Можаровський, А.Г. (Інститут електродинаміки НАН України, Київ, 2010)
The capability of construction, based on a single diagram, of the performance characteristics of transformer-key operation structures (TKOS) of regulators and stabilizers of alternating voltage due to their inherent property based on principle of invertibility has been substantiated. The features of calculating the installed capacity value of power sectioned autotransformers in the composition of TKOS of different alternating voltage transducers by wide variation of regulation (stabilization) width (depth) as well as its shift relative to nominal voltage have been researched. The findings are represented in the proposed volt-ampere diagrams which enable to evaluate the "contribution" to the value of rated autotransformer capacity of selected groups of its winding sections. References 4, table 1, figures 7.